KONSEP PENDIDIKAN ISLAM MUHAMMAD NATSIR (SuatuKajianAnalisisKritis) - La Rajab (al-Iltizam: Jurnal Pendidikan Agama Islam, 2016)
One of figure that is enough influential with its the education concept is M. Natsir. Tenacity and obstinacy done by him based on certain considerations, so that Salman Iskandar positions Natsir on course to 37 of 55 figures Muslim having an effect on in Indonesia. He is famous with movement of independence of RI, person that is simple and far from love to possession, spirit never give up and do not recognize hopeless. Most all masterpieces Natsir is nothing that specifically studies about education, more emphasizing is Islam study and its the elaborasi. But, there are some idea of Natsir touching about education, especially in book Capita Selekta, also in book Pendidikan, Pengorbanan, Leadership, Primordialism, and Nostalgia. Operates on education concept of Islam that is on the market his its is education that is in character integral, harmonious, and universal. Education having strong base and steady is not groggy and education of Islam having purpose of namely x'self slave (all done solely for having religious service) to God Swt. Added it to form Negara and prestigious and strong nation, hence required by teacher, loyal teacher, teacher readily sacrifices and struggles to educate the self-supporting and strong educative participants for the shake of kindness and nation taking place and state.